SISTEM INFORMASI PELAYANAN KESEHATAN BERBASIS WEB PADA KLINIK DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA - Achmad Solehuddin (2022)
The Regional Representative Council Clinic of the Republic of Indonesia is a health unit that provides free health services for employees and members of the DPD RI. The DPD RI Clinic provides general poly services, dental clinics and supporting health services such as physiotherapy, acupuncture and laboratories. The Regional Representative Board of the Republic of Indonesia Clinic in its health service process still uses a manual system. To register the patient must come directly to the clinic and queue first. In the process of processing and storing data, it is still done using paper documents which causes longer time for the clinic staff to search for data when needed. Therefore, it is necessary to have an information system that can support the health service process. The purpose of this study is to design and build a web-based health service information system that can assist the clinics of the Indonesian Regional Representatives Council in providing health services to patients. The method used to develop the system is a prototype. In this study, the system was built using the Codeigniter framework and MySQL database. The result of this study is a health service information system which is expected to facilitate the clinics of the Regional Representatives Council of the Republic of Indonesia in providing effective and efficient health services.